Using Online Modules to Build Capacity for Teacher Resilience - Beltman, Susan; Mansfield, C.; Wosnitza, M.; Weatherby-Fell, N.; Broadley, T. (Springer, 2018)
Teacher resilience is regarded as a complex, multidimensional, dynamic construct. Enhancing teacher resilience can potentially increase teacher commitment yet interventions to build resilience in pre-service programs are scarce. This chapter examines the effectiveness of the BRiTE (Building Resilience in Teacher Education) online modules to develop pre-service teachers’ capacity for resilience in Australia. The modules are briefly described. Perceptions of 146 final year pre-service teachers were gathered regarding resilience, self-efficacy, commitment and coping before completing the BRiTE modules and their final Professional Experience school placement. Both pre- and post-school placement measures were completed by 49 participants. To determine the impact of using the modules, matched data sets were divided with ‘users’ (n=32) scoring significantly higher scores than ‘non-users’ (n=17) on five post-placement survey scales. Despite some limitations, there was an indication that using the online modules assisted pre-service teachers develop their capacity for resilience. Adapting the modules for use with in-service teachers and other professional is an avenue for future research. This study has significance, given the importance of teacher professional resilience and suggests that interventions developed for pre-service contexts can make a difference.